Complete mitochondrial genome of Onchocerca lupi (Nematoda, Onchocercidae) - Chandler C. Roe; Jennifer Urbanz; Lela Andrews; Guilherme G. Verocai; David M. Engelthaler; Crystal M. Hepp; Jason W. Sahl (Mitochondrial DNA. Part B. Resources, 2021)
Onchocerca lupi, Rodonaja 1967, is an emerging, zoonotic filarial nematode parasite that causes ocular disease in dogs, cats, wild canids, and humans. It is the causative agent of ocular onchocercosis in canines with increasing incidence in both North America and the Old World during the early twenty-first century. We report the complete mitochondrial genome of an O. lupi isolate from a dog from Arizona, southwestern USA, and its genetic differentiation from related Onchocerca species. The whole mitochondrial genome was obtained from whole genome sequencing of genomic DNA isolated from an adult worm. This mitogenome is 13,766 bp in size and contains 36 genes and a control region. This mitogenome provides a valuable resource for future studies involving epidemiological surveillance, population genetics, phylogeography, and comparative mitogenomics of this emerging pathogen and other parasitic nematodes.